2021
DOI: 10.3847/1538-4357/ac2307
|View full text |Cite
|
Sign up to set email alerts
|

The Atacama Cosmology Telescope: A Search for Planet 9

Abstract: We use Atacama Cosmology Telescope (ACT) observations at 98 GHz (2015–2019), 150 GHz (2013–2019), and 229 GHz (2017–2019) to perform a blind shift-and-stack search for Planet 9. The search explores distances from 300 au to 2000 au and velocities up to 6.′3 per year, depending on the distance (r). For a 5 Earth-mass Planet 9 the detection limit varies from 325 au to 625 au, depending on the sky location. For a 10 Earth-mass planet the corresponding range is 425 au to 775 au. The predicted aphelion and most like… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…While faint at optical wavelengths, the putative Planet 9 could be detected from its thermal emission in the far-infrared and microwave. Although Naess et al (2021a) reported no significant detection, they were able to shrink the allowed parameter space by 17% and 9% for 5 and 10 M ⊕ planets, respectively. With increased sensitivity and longer time baselines, SO data can complement and extend this analysis.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…While faint at optical wavelengths, the putative Planet 9 could be detected from its thermal emission in the far-infrared and microwave. Although Naess et al (2021a) reported no significant detection, they were able to shrink the allowed parameter space by 17% and 9% for 5 and 10 M ⊕ planets, respectively. With increased sensitivity and longer time baselines, SO data can complement and extend this analysis.…”
Section: Discussionmentioning
confidence: 91%
“…A recent study employing ACT data has demonstrated the utility of CMB telescopes for studying the solar system (Naess et al 2021a). Based on the clustering of Kuiper Belt objects, it has been proposed that a 5-10 M ⊕ Planet 9 may be orbiting the Sun at 400-800 au (Batygin & Brown 2016;Batygin et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Clearly, in the continuing absence of direct observation, e.g. [4]; other supporting evidence would be welcome.…”
Section: Introductionmentioning
confidence: 96%
“…Although the Planck Collaboration has previously published detections of asteroids in their analysis connecting dust observations to asteroid families (Cremonese et al 2002;Planck Collaboration et al 2014) and the Atacama Cosmology Telescope (ACT) collaboration masked asteroids in their search for Planet 9 (Naess et al 2021), this work represents the first focused analysis of asteroid flux in data from an experiment designed to measure the CMB. With continued analysis, historic and future data measuring the CMB can provide more observations of asteroids at submillimeter and millimeter wavelengths.…”
Section: Introductionmentioning
confidence: 96%